PENGARUH PENGGUNAAN GADGET DAN LINGKUNGAN TEMAN SEBAYA TERHADAP MINAT BELAJAR SISWA KELAS VII PADA MATA PELAJARAN IPS - Mariana Erlin Wasa; Sulistyo Sulistyo; Affan Afian (Jurnal Riset Pendidikan Ekonomi, 2019)
Interest in learning is an encouragement that students have to carry out learning activities in order to achieve goals in the learning process. The purpose of this study was to determine the significant and partially simultaneous influence between the use of gadgets and the environment of peers on the learning interest of Grade VII students in Social Sciences subjects at SMP Negeri 17 Malang. this type of research uses ex post facto research using multiple linear regression. This research was conducted in SMP Negeri 17 Malang with a population of 268 students and a sample of 54 students. proportional random sampling technique. Data collection using a questionnaire. Based on the calculation results, it is known that: 1) there is an influence of the use of gadgets and peers' environment on the learning interests of Grade VII students in Social Sciences subjects at SMP Negeri 17 Malang; 17 Malang, 3) there is an influence of peers 'environment in class VII students' social studies interest in Social Sciences at SMP Negeri 17 Malang.